(untitled) (American Journal of Interdisciplinary Research and Development, 2022)
In modern societies, as a result of the acceleration of intercultural communication and the strengthening of interaction, relatively few peoples are influenced by the majority, and in some respects, they completely lose their identity, and they are lost at the expense of the majority. being observed. The issues of self-awareness are explained in the scientific language by the term "ethnic identity". This article talks about the socio-psychological features of ethnic identity based on the issues mentioned above.